2015
DOI: 10.1038/srep12363
|View full text |Cite
|
Sign up to set email alerts
|

Rap2B promotes proliferation, migration and invasion of human breast cancer through calcium-related ERK1/2 signaling pathway

Abstract: Rap2B, a member of GTP-binding proteins, is widely upregulated in many types of tumors and promotes migration and invasion of human suprarenal epithelioma. However, the function of Rap2B in breast cancer is unknown. Expression of Rap2B was examined in breast cancer cell lines and human normal breast cell line using Western blot analysis. Using the CCK-8 cell proliferation assay, cell cycle analysis, and transwell migration assay, we also elucidated the role of Rap2B in breast cancer cell proliferation, migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 45 publications
1
68
1
Order By: Relevance
“…Subsequently, the plasmid of si-MDM2 was transfected into MP65 cells to silence MDM2 expression, and the transfection efficiency was shown in Figure 6f. Results in (Di et al, 2015). Recent study shows that activation of the ERK1/2 pathway is a common event in uveal melanoma .…”
Section: Ras-erk1/2 Pathway Degrades Tip60 By the Mediation Of Mdm2mentioning
confidence: 98%
“…Subsequently, the plasmid of si-MDM2 was transfected into MP65 cells to silence MDM2 expression, and the transfection efficiency was shown in Figure 6f. Results in (Di et al, 2015). Recent study shows that activation of the ERK1/2 pathway is a common event in uveal melanoma .…”
Section: Ras-erk1/2 Pathway Degrades Tip60 By the Mediation Of Mdm2mentioning
confidence: 98%
“…Among these pathways, such as the 'PI3K-Akt signaling pathway', is involved in the carcinogenesis of gastric adenocarcinoma metastases (21), the 'Wnt signaling pathway' has been investigated as a cause of adenocarcinoma invasion (22) and the gene category 'Pathways in cancer' is involved in the development of GC. In addition, some pathways such as 'Small cell lung cancer, Cell adhesion molecules (CAMs), Proteoglycans in cancer and Transcriptional regulation in cancer' were also reported as cancers related pathways (23,24) (Fig. 5).…”
Section: Go and Pathway Analysis Of Differentially Expressed Genesmentioning
confidence: 99%
“…Previous work demonstrated that Rap-2b is a target of p53 and it counteracts p53-mediated apoptosis [72]. Moreover, Rap-2b can affect cytoskeleton reorganisation and cell migration [73,74]. Given the role of Rap-2b in transformation, it may be that upregulation of this gene contributes to AAI-induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%